Prediksi Persediaan Minyak Bumi Menggunakan Model Dinamis Distribusi Lag, Dinamis Autoregressive , dan Autoregressive Distribusi - Hary Merdeka; Helma Helma; Yenni Kurniawati (Journal of Mathematics UNP, 2021)
Abstract – Energy security is the availability of energy sources that are not disconnected at an affordable price. Problems that occur in energy security in Indonesia is an imbalance in the production of petroleum consumption in Indonesia. Therefore the aim of this study to predict the oil supplies for several years later.  Based on the results obtained from the model distribution autoregressive lag model . a petroleum supplies,  petroleum consumption in the two previous periods, and oil production earlier period. From the model can be predicted that oil supplies in 2014 and 2015 respectively amounting to 3.112.002 and 3.335.348 terajoule. This model depicts the predictions of inventory that is influenced by petroleum consumption in the two previous periods and production of petroleum in the previous period amounted to 98.28%. Keywords – Energy security, lag distributiondynamic models, dynamicautoregressive, distribution autoregressive lag, ARDL.